Safety and Effectiveness of Externalized Ureteral Catheter in Tubeless Percutaneous Nephrolithotomy - Raharja, Putu Angga Risky; Atmoko, Widi; Rasyid, Nur; Birowo, Ponco (Urology Journal, 2019)
Purpose: To review the safety and effectiveness of tubeless percutaneous nephrolithotomy (PCNL) with an externalized ureteral catheter (EUC) compared with standard PCNL with nephrostomy tube and tubeless PCNL with double-J (DJ) stent following uncomplicated PCNL and the absence of residual stones. Materials and Methods: Patients with kidney stones who underwent uncomplicated PCNL between January 2000 to December 2017 and had no residual stones were retrospectively evaluated. The 766 patients were divided into standard PCNL with nephrostomy tube (group 1; 350 patients), tubeless PCNL with DJ stent (group 2; 189 patients), and tubeless PCNL with EUC (group 3; 227 patients). Demographic characteristics, stone-related factors, perioperative and postoperative parameters were analyzed. Results: Demographic and stone-related characteristics were comparable. The differences in the mean operative time and complication rates were not significant. Postoperative hospitalization period was shorter in group 3 (3.19 ± 2.2 days) compared with group 1 (4.12 ± 2.4 days; p < .001) but not to that of group 2 (3.44 ± 2.8 days; p = .680). Postoperative pain score was lower in group 3 (3.24 ± 1.1) compared with both group 1 (6.36 ± 1.7; p < .001) and group 2 (4.85 ± 1.1; p < .001). Urine leakage complication was lower in group 3 (0.4%) compared with group 1 (2.9%, p = .038) but not to that of group 2 (0.5%; p = .897). Conclusions: Tubeless PCNL is effective and safe for uncomplicated PCNL in the absence of residual stones. Tubeless PCNL with EUC is associated with decreased pain, hospitalization time, and urine leakage compared with standard PCNL. However, it is only associated with decreased pain when compared with tubeless PCNL with DJ stent.